Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1128/mcb.01286-08
|View full text |Cite
|
Sign up to set email alerts
|

Pak4, a Novel Gab1 Binding Partner, Modulates Cell Migration and Invasion by the Met Receptor

Abstract: Hepatocyte growth factor (HGF), the ligand for the Met receptor tyrosine kinase, induces epithelial cell dispersal, invasion, and morphogenesis, events that require remodeling of the actin cytoskeleton. The scaffold protein Gab1 is essential for these biological responses downstream from Met. We have identified p21-activated kinase 4 (Pak4) as a novel Gab1-interacting protein. We show that in response to HGF, Gab1 and Pak4 associate and colocalize at the cell periphery within lamellipodia. The association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 56 publications
(87 reference statements)
4
72
0
Order By: Relevance
“…MET encodes a tyrosine kinase receptor that is associated with cancer progression (73,74). In a recent study, the amplification of MET was observed in patients with GC, and was indicative of the likelihood of tumor invasion and LN metastasis (75).…”
Section: Other Mechanismsmentioning
confidence: 99%
“…MET encodes a tyrosine kinase receptor that is associated with cancer progression (73,74). In a recent study, the amplification of MET was observed in patients with GC, and was indicative of the likelihood of tumor invasion and LN metastasis (75).…”
Section: Other Mechanismsmentioning
confidence: 99%
“…This is consistent with their roles in controlling cell survival, proliferation, cytoskeletal organization, and migration. 74,[83][84][85][86][87][88][89] Neither the group A nor the group B Paks are frequently mutated in human cancer. Instead, overexpression and gene amplification of the Pak kinases, however, are commonly seen in cancer.…”
Section: Paks and Cancermentioning
confidence: 99%
“…Met activation is also linked to pathways that modulate the actin cytoskeleton, cell adhesion and migration (Peschard and Park, 2007). These are coordinated through Gab1, where recruitment of Crk to Gab1 couples Met signalling to activation of Rap1 and Rac (Lamorte et al, 2002b;Rodrigues et al, 2005), and Gab1-Pak4 interaction is required for the localisation of Pak4 to lamellipodia and cell invasion (Paliouras et al, 2009). In epithelial colonies, Gab1 localises to lamellipodia with downstream proteins, such as Shp2, for prolonged periods (up to 15 minutes) following HGF stimulation (Frigault et al, 2008;Kallin et al, 2004;Maroun et al, 1999a).…”
Section: Introductionmentioning
confidence: 99%